Mulheres, política e resistência: trajetórias de vereadoras da região sudoeste do Paraná - Freese, Marilia Zimermann (2024)
This dissertation analyzed the political trajectories of female councilors in the Southwest Region of Paraná, in a context of great disparity between women and men in the occupation of elected positions. The aim was to understand the paths taken by elected female councilors. Initially, a quantitative survey was conducted, through which all women who had been elected councilors in the history of the region's municipalities since 1947 were identified. From then on, the research followed a qualitative analysis, using the life history method, with an emphasis on the political trajectories of six female councilors who had already served three or more terms. The analysis of these trajectories sought to identify the routes women took to becoming councilors, how they experience or have experienced their legislative mandates, and the gender issues that affect their political representation. The research was theoretically based on Decolonial Studies and the feminist perspective as an analytical lens to understand women's experiences based on their speeches, positions, memories, and participation. The results of the research show that women who were elected and reelected for three or more terms are all white, linked to the hegemonic religion and who have a significant level of education (high school or higher education). The routes these women took to becoming councilors are strongly influenced by family members already involved in political life, although this is not the only factor. The study also identified other aspects related to the experience of being a councilor, the challenges related to the assignment of domestic and care work, the political gender violence to which they are subjected and how women resist it.